EVALUATION OF THE TECHNICAL PARAMETERS OF SPORTS ACTIVITY OF THE WOMEN'S TEAM OF THE MONGOLIAN STUDENT BASKETBALL LEAGUE - Gantulga, R.; Erdenepurev, L. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to conduct a statistical analysis of the main technical parameters, such as the accuracy of the throw, the effectiveness of the transfer and possession of the ball, among the players of the women's team "Shonkhoruud" (falcons) of the "Student League" of the Mongolian State University. Methods and structure of the study. We determined and compared the performance and results of accurate shots, the effectiveness of passes, interceptions and blocking of balls of the last 12 games of the Student League season based on statistics and match facts. Results and conclusions. In terms of the offensive performance of the "Shonkhoruud" team, 46.1% of the players made two-point shots, that is, indicators below the team average, 15.3% did not make three-point shots at all, and 30.7% made these shots, but did not hit the target, which indicates that the offensive team was insufficient. In terms of assists, the team completed 50% of assists out of 12 matches, above the team average, and 30.7% of players assisted other players, increasing the possibility of high scores.